2017
DOI: 10.1038/s41598-017-02284-0
|View full text |Cite
|
Sign up to set email alerts
|

Combined magnetron sputtering and pulsed laser deposition of TiO 2 and BFCO thin films

Abstract: We report the successful demonstration of a hybrid system that combines pulsed laser deposition (PLD) and magnetron sputtering (MS) to deposit high quality thin films. The PLD and MS simultaneously use the same target, leading to an enhanced deposition rate. The performance of this technique is demonstrated through the deposition of titanium dioxide and bismuth-based perovskite oxide Bi2FeCrO6 (BFCO) thin films on Si(100) and LaAlO3 (LAO) (100). These specific oxides were chosen due to their functionalities, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…There have been several reports combining MS and PLD (MSPLD) for the deposition of thin films for materials such as carbides and diamond-like carbon films [22], ternary wolfram borides [23] or tin oxide films [24]. The advantages of the combined MS and PLD deposition is a smoother surface [24] and a denser and higher hardness of the obtained films [23].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports combining MS and PLD (MSPLD) for the deposition of thin films for materials such as carbides and diamond-like carbon films [22], ternary wolfram borides [23] or tin oxide films [24]. The advantages of the combined MS and PLD deposition is a smoother surface [24] and a denser and higher hardness of the obtained films [23].…”
Section: Introductionmentioning
confidence: 99%
“…There have been some published reports on combining MS and PLD for the deposition of carbides and diamond-like carbon films [35], tin oxide films [36], GST-225 [37], and ternary wolfram borides [38]. Simultaneous MS and PLD deposition can lead to a denser film [36] with a smoother surface [38].…”
Section: Introductionmentioning
confidence: 99%
“…Materials of ceramic coating on the structural materials is one of the candidates of high temperature materials for the deployment of advanced nuclear reactors and applications in many fields [5][6][7][8][9][10]. There are many techniques for the ceramic coating such as plasma spray coating [5], electrophoretic deposition (EPD) [6] and pulsed laser deposition (PLD) [7][8][9][10]. One of the issues for the ceramic coating is formation of the roughness and micro porous.…”
Section: Introductionmentioning
confidence: 99%
“…One of the issues for the ceramic coating is formation of the roughness and micro porous. It has been reported that the PLD technique has advantage for minimize the micro porous [7][8][9][10]. In the utilization of the coating material especially for the deployment of advanced nuclear reactors, it is very important to select the substrate materials for ceramic coating as the base materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation